Histological findings in resected leiomyomas following MR-HIFU treatment, single-institution data from seven patients with unfavorable focal therapy - Antti Viitala; Michael Gabriel; Kirsi Joronen; Gaber Komar; Antti Perheentupa; Teija Sainio; Jutta Huvila; Pekka Pikander; Pekka Taimen; Roberto Blanco Sequeiros (International Journal of Hyperthermia, 2023)
AbstractPurpose Magnetic resonance – high-intensity focused ultrasound (MR-HIFU) is a noninvasive treatment option for symptomatic uterine leiomyomas. Currently, pretreatment MRI is used to assess tissue characteristics and predict the most likely therapeutic response for individual patients. However, these predictions still entail significant uncertainties. The impact of tissue properties on therapeutic outcomes remains poorly understood and detailed knowledge of the histological effects of ultrasound ablation is lacking. Investigating these aspects could aid in optimizing patient selection, enhancing treatment effects and improving treatment outcomes.Methods and materials We present seven patients who underwent MR-HIFU treatment for leiomyoma followed by second-line surgical treatment. Tissue samples obtained during the surgery were stained with hematoxylin and eosin, Masson’s trichrome and Herovici to evaluate general morphology, fibrosis and collagen deposition of leiomyomas. Immunohistochemical CD31, Ki-67 and MMP-2 stainings were performed to study vascularization, proliferation and matrix metalloproteinase-2 protein expression in leiomyomas, respectively.Results The clinical characteristics and radiological findings of the leiomyomas prior to treatment as well as qualitative histological findings after the treatment are presented and discussed in the context of current literature. A tentative model for volume reduction is presented.Conclusion These findings provide insights into potential factors contributing to suboptimal therapeutic outcomes and the variability in histological changes following treatment.